Menjaga Kepercayaan Dalam Transaksi Keuangan: Pengaturan Prinsip Kepercayaan di Bank - Saputra, Angga (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The importance of maintaining trust in financial transactions is very crucial, especially in the banking sector. As a financial institution that acts as an intermediary in financial transactions, banks have a great responsibility in maintaining the trust of their customers. Therefore, the regulation of trust principles in banks is very important to be carried out in order to maintain trust and security in financial transactions. This study aims to study the regulation of trust principles in banks and the efforts made by banks in maintaining customer trust. The results of this study indicate that banks make efforts to maintain customer trust by supervising the security of financial transactions, building a good image, and providing transparent information to customers.